الدين والتدين في الخطاب الإسلامي المعاصر في مصر - توري، سيكو مارفا أبو بكر (al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2013)
The research attempts to shade light on Islam from a new theoretical and semantic approach, in order to further elaborate about the nature of religions in general and Islam in particular. Hence, the research puts forward the hypothesis that Islam has two dimensions; Religion, and Religiosity. On the one hand, Islam is religion because it contains a number of beliefs, and faith elements, of which the door is opened for a person to enter Islam. Similarly, the religion-based dimension differentiates between the Muslims and the adherents to other religions. On the other hand, Islam is alos based on the concept of religiosity, as that person who submitted to the first dimension -faith- would like (or should struggle, and work hard) to implement his or her daily activities from all its aspects upon the measurement of the first Dimension (Faith). This research examines religion and religiosity from a contemporary Islamic discourse, utilizing Egypt as case study. This limitation is due to several factors, taking into consideration the fact that the Islamic discourse in Egypt is representative of Islamic discourse worldwide. Furthermore, this research focuses on three popular trends of Islamic thought in Egypt: the Islamic Movements, the Islamic moderate trend, and lastly the Islamic rational-philosophical trend. The first is represented through the works of Syed Qutb; the second is represented by Yusuf al-Quardawi, and the last not the least by Hassan Hanafi. Through this research, the reader will come across the concept and the nature of religion as it is represented within the aforementioned trends of thought, as well as the concept of religiosity and its related matters. The researcher's personal analysis regarding this issue concludes the research. Then to follow up with the result of the research of which looking to Islam, as religion and religiosity is one among them. Moreover, concept of Religion in the discourses of the research is faith in general and Islam in particular, and it is known in the field of Islamic theology. Another result of the study is that concept of Religiosity is the applied part of faith while turning theories into action; and it is addressed under Islamic law.